The The Impact of Antidiabetic Dose Appropriateness Based on Renal Function on Therapeutic Outcomes among Geriatric at Bali, Indonesia - Bagus N. Sugiastana; Phebe Hendra; Dita Maria Virginia (Universitas Airlangga, 2025)
Background: Diabetes mellitus is a significant global health issue, especially in the older population. Appropriate drug dosing is crucial in geriatric patients because renal function generally declines with age. A decline in renal function is directly associated with the adverse effects of antidiabetic drugs, particularly hypoglycemia, rather than their therapeutic efficacy. Objective: The objective of the present study was to assess the effect of antidiabetic dose appropriateness according to renal function on therapeutic outcomes among geriatric patients at three hospitals in Bali Province. Methods: The research was designed as an observational analytic study with a cross-sectional design. The study involved patients with diabetes aged ≥ 60 years, with or without renal function impairment. Medical records from January to December 2024 were also reviewed for this study. The suitability of antidiabetic drug dosing was evaluated using the estimated glomerular filtration rate (eGFR) calculated using the Cockcroft–Gault equation. The prescribed doses were compared with the dosage guidelines based on the renal function. A Chi-square analysis was performed to assess the relationship between the appropriateness of the antidiabetic dose and the therapeutic outcomes. Moreover, multivariate analysis was performed using logistic regression after adjusting for other factors. Results: Among the included patients, 27.6% were diagnosed with CKD and 28.4% had renal function classified as stage G2. A total of 51.5% of patients received appropriately adjusted antidiabetic doses. Dose appropriateness was significantly associated with primary clinical outcomes (p<0.05) but not with secondary clinical outcomes. Conclusion: In conclusion, appropriate dose adjustment is essential for enhancing diabetes treatment strategies for geriatric patients with diverse stages of kidney dysfunction.